Gigantic GIST: A Case of the Largest Gastrointestinal Stromal Tumor Found to Date - Abdalla Mohamed; Youssef Botros; Paul Hanna; Sang Lee; Walid Baddoura; Jamshed Zuberi; Tanuja Damani (Case Reports in Surgery)
Gastrointestinal stromal tumors are uncommon when compared to all gastrointestinal neoplasms but are the most common mesenchymal tumors of the gastrointestinal tract. The largest gastrointestinal stromal tumor ever recorded in literature weighed approximately 6.1 kg and measured 39 cm × 27 cm × 14 cm. About two-thirds of GISTs are malignant. The tumor size, mitotic rate, cellularity, and nuclear pleomorphism are the most important parameters when considering prognosis and recurrence. The definitive treatment for these tumors is resection. In the year 2000, the first patient was treated with the tyrosine kinase inhibitor imatinib and since then, gastrointestinal stromal tumors with high-risk features have been treated successfully with tyrosine kinase inhibitors. We present the largest gastrointestinal stromal tumor recorded in medical literature measuring 42.0 cm × 31.0 cm × 23.0 cm in maximum dimensions and weighing in at approximately 18.5 kg in a 65-year-old African-American male who presented with increased abdominal distention. The mass was successfully excised, and the patient was treated with imatinib without local or distant recurrence 1.5 years postoperatively.